The Effect Of Motivation And Internship Experience On Culinary Students’ Work Readiness At Vocational High School - Maharani, Nindi Putri; Handajani, Sri; Nurfatimah, Ratna Palupi; Romadhoni, Ita Fatkhur (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
This study aims to analyze the influence of motivation and internship (PKL) experience on the work readiness of culinary students at SMK Negeri 8 Surabaya. Grounded in Maslow’s hierarchy of needs and Kolb’s experiential learning theory, both factors are considered essential components in shaping students’ employability. This research employed a quantitative correlational method with a sample of 62 eleventh-grade culinary students selected through random sampling. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression using SPSS 26.  The results indicate that motivation and internship experience have a positive and significant effect on students’ work readiness, both partially and simultaneously. The regression model produced an Adjusted R² value of 0.583, indicating that 58.3% of the variance in work readiness is explained by the two predictor variables.